2013
DOI: 10.1002/jmri.24385
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast enhanced-MRI in rectal cancer: Inter- and intraobserver reproducibility and the effect of slice selection on pharmacokinetic analysis

Abstract: Our results indicate good inter- and intraobserver reproducibility for most pharmacokinetic parameters and for the two adjacent slices measured. However, as there were some parameters that demonstrated poor correlation, testing for reproducibility and a multiobserver approach might be considered whenever using pharmacokinetic parameters as biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our own recent investigation concurs with prior literature which has shown some promise using this parameter with regard to tumor response [3]. Since there may be intrinsic tumor heterogeneity of neovascularity, as with water proton mobility, the method of measurement of the tumor ROI by the radiologist will affect this metric as well [4]. For both DWI and DCE-MRI, we hypothesize that the interrogation of the entire lesion would reflect tumor biology, including tumor environment heterogeneity, if present and would be reproducible and show correlation with pathologic response.…”
Section: Introductionsupporting
confidence: 83%
“…Our own recent investigation concurs with prior literature which has shown some promise using this parameter with regard to tumor response [3]. Since there may be intrinsic tumor heterogeneity of neovascularity, as with water proton mobility, the method of measurement of the tumor ROI by the radiologist will affect this metric as well [4]. For both DWI and DCE-MRI, we hypothesize that the interrogation of the entire lesion would reflect tumor biology, including tumor environment heterogeneity, if present and would be reproducible and show correlation with pathologic response.…”
Section: Introductionsupporting
confidence: 83%
“…Kim et al [31] showed that the K trans parameter (contrast agent transfer constant between plasma space to extracellular extravascular space) had a large decrease in the mean value after CRT and this was associated with a good therapeutic response to CRT for LARC. However, being influenced by many factors, many different models are still present in the literature and their high output variability reflects a poor clinical reliability [8,16,18,32]. Results of quantitative analysis to assess therapy response on 3T MR scanners are more promising, as was reported in the studies of Intven et al [33] and Lim et al [34].…”
Section: Discussionmentioning
confidence: 89%
“…We found a significant positive correlation between in vivo microvascular permeability calculated from both 3D and 2D DCE‐MRI and permeability calculated from ex vivo NIRF with EB. For both 3D and 2D sequences, we evaluated temporal stability metrics , intra‐ and inter‐observer reproducibility (see Supporting Information) and correlation with ex vivo permeability. Among 3D sequences, 3D TFE DCE‐MRI showed superior tSNR and tCNR, whereas both 3D TFE and TSE DCE‐MRI showed significant correlation with ex vivo NIRF and good intra‐ and inter‐observer reliability.…”
Section: Discussionmentioning
confidence: 99%